Amino acid diversity on the basis of cytochrome b gene in Kacang and Ettawa Grade goats - D. A. Lestari; S. Sutopo; E. Kurnianto (Diponegoro University, 2017)
The objectives of study were to identify and assess the amino acid diversity of Cytochrome b (Cyt b) gene, genetic marker and characteristic of specific amino acid in Kacang and Ettawa Grade goat. Nineteen heads of Kacang goat (KG) and twelve heads of Ettawa Grade goat (EG) were purposively sampled. The genomic DNA was isolated by Genomic DNA Mini Kit (Geneaid) and amplified Cyt b using PCR method with CytbCapF and CytbCapR primers and was sequenced. The results showed that there were two specific amino acids that distinguish KG and EG goat with C. hircus and C. aegagrus and four specific amino acids that distinguish KG and EG goat with C. falconeri, but there were no specific amino acids can be used as a genetic marker to distinguish between Kacang and EG goat. In conclusion, specific amino acids in Cyt b gene can be used as a genetic marker among KG and EG goat with 3 goat others comparator.